Meta-QTL analysis reveals the important genomics regions for biotic stresses, nutritional quality and yield related traits in pearl millet - Shreshth Gupta; Sagar Krushnaji Rangari; Aakash Sahu; Yogesh Dashrath Naik; C. Tara Satayavathi; Somashekhar Punnuri; Mahendar Thudi (CABI Agriculture and Bioscience)
Abstract Pearl millet (Cenchrus americanus) is the sixth most significant cereal crop cultivated on 30 million ha and a staple diet for 90 million poor people across the globe. Besides abiotic stresses several biotic stresses have been limiting production of pearl millet in the semi-arid and arid regions. Although, the Quantitative Trait Loci (QTLs) associated with key diseases like blast, rust and downy mildew resistance and nutritional content has been reported, the use of these QTLs is limited in breeding programs. To identify highly stable consensus genomic regions, we conducted Meta-QTL analysis using 191 QTLs reported in 12 independent studies over the last two decades. As a result, we report 34 Meta-QTLs regions on a consensus genetic map comprising of 692 markers and spanning 2070.7 cM. The confidence interval of Meta-QTLs was reduced by 3.63 folds (0.18–7.49 cM), in contrast to projected QTLs interval of 1.11–60.63 cM. Further, a total of 1198 genes were identified in 34 Meta-QTL regions. Among 34 Meta-QTL regions, Meta-QTL1.1 is found to be region of significant importance as it harbours genes for enhanced biotic stress tolerance, plant growth and development as well as genes related with enhanced seed development. Meta-QTL2.4 has highest number of genes with a significant role in disease resistance which contains basic leucine zipper domain, zinc family, leucine rich repeat regions. Meta-QTL3.1 has ABC transporter like activity coupled with the ATPase activity which has a role in Fe and Zn uptake in leaves and root tissues. These Meta-QTL regions can be used in genomics-assisted breeding for enhancing the blast, rust downy mildew resistance as well as yield and nutritional traits.